An extended helical conformation in domain 3a of Munc18-1 provides a template for SNARE (Soluble N-Ethylmaleimide-sensitive Factor Attachment Protein Receptor) complex assembly - Parisotto, Daniel; Pfau, Maximilian; Malsam, Andrea; Wild, Klemens; Mayer, Matthias P.; Malsam, Jörg; Sinning, Irmgard; Söllner, Thomas (The journal of biological chemistry, 2014)
Munc18-1, a SEC1/Munc18 protein and key regulatory protein in synaptic transmission, can either promote or inhibit SNARE complex assembly. Although the binary inhibitory interaction between Munc18-1 and closed syntaxin 1 is well described, the mechanism of how Munc18-1 stimulates membrane fusion remains elusive. Using a reconstituted assay that resolves vesicle docking, priming, clamping, and fusion during synaptic exocytosis, we show that helix 12 in domain 3a of Munc18-1 stimulates SNAREpin assembly and membrane fusion. A single point mutation (L348R) within helix 12 selectively abolishes VAMP2 binding and the stimulatory function of Munc18-1 in membrane fusion. In contrast, targeting a natural switch site (P335A) at the start of helix 12, which can result in an extended α-helical conformation, further accelerates lipid-mixing. Together with structural modeling, the data suggest that helix 12 provides a folding template for VAMP2, accelerating SNAREpin assembly and membrane fusion. Analogous SEC1/Munc18-SNARE interactions at other transport steps may provide a general mechanism to drive lipid bilayer merger. At the neuronal synapse, Munc18-1 may convert docked synaptic vesicles into a readily releasable pool.
Gesehen am 04.09.2020